The relationship of conditioning experiences to strength of fear,anxiety responses and fear-onset memories : an examination of Rachman's three-pathways theory : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in psychology at Massey University - Withers, Rody Desmond (Massey University, 1994)
The purpose of the present study was twofold: First, to test Rachman's (1977) theory which predicts that "direct" conditioned fears will differ from "indirect" conditioned fears in magnitude and anxiety response patterns. Secondly, to explore validity issues related to the questionnaire methodology typically used in fear acquisition research. The questionnaire comprised three anxiety scales and three fear-onset questions used in prior research, a specifically developed 36-item fear list and two validity-check items. One hundred and ninety-one subjects completed the questionnaire. After selecting and rank-ordering ten fears from the fear list, subjects answered questionnaire items for their first- and then their tenth- ranked fear. Results failed to confirm Rachman's predictions: A significantly greater proportion of subjects ascribed highly-feared and moderately-feared situations or things to direct conditioning. In addition, differential anxiety response patterns were not present for different levels of fear. However, results supported the prediction that direct-conditioning ascriptions would be endorsed with greater certainty. The findings suggest that direct-conditioning experiences may be more memorable than indirect-conditioning events. The theoretical and methodological implications of the findings are discussed. It is suggested that future research either employ methodologies more suited to investigating causal relationships or that Rachman's (1977) theory be blended with an attributional account of fear acquisition.
Keywords: Anxiety; Courage; Conditioned fear; Conditioning (Psychology); Stanley Rachman; Cognition; Fear